2000
DOI: 10.1081/ddc-100101289
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Hydrocolloids: Principal Component Analysis Applied to the Study of Correlations Between Parameters Describing the Consistency of Hydrogels

Abstract: This work was part of a pure research project on the functionalization of three families of hydrocolloids: cellulose derivatives, carrageenates, and alginates. Principal component analysis (PCA), a powerful statistical method, was used to demonstrate the relations existing among these different parameters that describe the consistency of hydrogels and their spreadability. This approach therefore provides a basis for modeling hydrogel consistency. PCA also afforded a classification of hydrogels that demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…These results pointed out that the different lipophilicity of oils and emulsifiers could not account for the obtained S values, suggesting that ingredients' interactions occurring in the emulsion structure could determine different textures, which affected formulation spreadability. Other authors reported a linear relationship between viscosity and spreadability for topical formulations [24,25] as the lower the viscosity of a cream, the lower the surface tension and the higher the spreadability on the skin. The lack of a relationship between emulsions' viscosity and in vitro spreadability observed in our study could be due to the method we chose to perform in vitro spreadability measurements.…”
Section: Physicochemical Properties Of Emulsions A-cmentioning
confidence: 99%
“…These results pointed out that the different lipophilicity of oils and emulsifiers could not account for the obtained S values, suggesting that ingredients' interactions occurring in the emulsion structure could determine different textures, which affected formulation spreadability. Other authors reported a linear relationship between viscosity and spreadability for topical formulations [24,25] as the lower the viscosity of a cream, the lower the surface tension and the higher the spreadability on the skin. The lack of a relationship between emulsions' viscosity and in vitro spreadability observed in our study could be due to the method we chose to perform in vitro spreadability measurements.…”
Section: Physicochemical Properties Of Emulsions A-cmentioning
confidence: 99%
“…The diameters of resulting circles (ɸ) were 38.0 ± 1.0 mm and 37.3 ± 0.6 mm for BG20 and BG30, respectively. In a study on various oil-in-water creams and gels, Arvouet-Grand et al [20] and later Lardy et al [21] introduce the terms 'semistiff' and 'semi-fluid' to evaluate the spreadability of creams and gels. According to both classifications, BG20 and BG30 are semi-stiff formulations, because the established (ɸ) was ≤ 50 mm.…”
Section: Determination Of the Spreadability Of Bigel Formulationsmentioning
confidence: 99%
“…The spread diameter (ɸ) was measured after 1 min [19][20][21]. The measurements were performed three times and the results were recorded as the mean ± SD [5].…”
Section: Determination Of the Spreadability Of Bigel Formulationsmentioning
confidence: 99%
“…The spread diameter (Φ) was measured after 1 min. [29][30][31][32] The measurements were done 3 times, and the results were represented as a mean value ± SD.…”
mentioning
confidence: 99%